2017
DOI: 10.1039/c7sc02691a
|View full text |Cite|
|
Sign up to set email alerts
|

What is the fundamental ion-specific series for anions and cations? Ion specificity in standard partial molar volumes of electrolytes and electrostriction in water and non-aqueous solvents

Abstract: Consistent trends in ion-specificity across many solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
130
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(139 citation statements)
references
References 83 publications
8
130
1
Order By: Relevance
“…[8][9] Specific ion effects make modeling these processes difficult; a thorough understanding of the molecular-scale interactions that govern them is necessary. 10 Here, vibrational sum frequency generation (VSFG) spectra reveal a novel interfacial water structure due to the adsorption of PtCl6 2complexes at a soft charged interface. MD simulations show that this structure is due to PtCl6 2partially retaining its hydration sphere after closely adsorbing to the interface.…”
Section: Introductionmentioning
confidence: 98%
“…[8][9] Specific ion effects make modeling these processes difficult; a thorough understanding of the molecular-scale interactions that govern them is necessary. 10 Here, vibrational sum frequency generation (VSFG) spectra reveal a novel interfacial water structure due to the adsorption of PtCl6 2complexes at a soft charged interface. MD simulations show that this structure is due to PtCl6 2partially retaining its hydration sphere after closely adsorbing to the interface.…”
Section: Introductionmentioning
confidence: 98%
“…23 In order to evaluate the salt effect, we performed reactions with a salt known to have a salt-out (LiCl) or salt-in (KCl) effect based on the Hofmeister series with a higher salt concentration (400 mM). 25 These experiments indicated that for both the hydrazone and oxime-formation reactions, LiCl accelerated the reaction rate, suggesting a salt-out effect, whereas KCl reduced the rate as compared to the NaCl catalyzed reaction ( Fig. 2c and d).…”
Section: Resultsmentioning
confidence: 79%
“…On the same manner, similar densities correspond to similar solid residue values, the slightly higher density observed for Acqua Rocchetta being in line with its solid residue which slightly higher than that of the Reference Mineral Water. Thus, it seems that the ions total amount is the fundamental properties in regulating the density of mineral water; specific effects exerted by selected ions, reported in the literature (Mazzini & Craig, 2017), play a minor role.…”
Section: Resultsmentioning
confidence: 99%